Synthesis of a biocompatible benzophenone-substituted chitosan hydrogel as novel coating for PEEK with extraordinary strong antibacterial and anti-biofilm properties. (December 2022) - Borgolte, M.; Riester, O.; Quint, I.; Blendinger, F.; Bucher, V.; Laufer, S.; Csuk, R.; Scotti, L.; Deigner, H.-P.
Abstract: Chitosan derivatives substituted with benzophenone groups that can be cross-linked by ultraviolet light were synthesized as coatings for PEEK substrates used in the construction of lumbar cages. The IC90 values of the benzophenone-modified chitosan polymers in solution before crosslinking were in the same range as those reported for native chitosan. The resulting hydrogel surface after crosslinking exhibited excellent antimicrobial properties and was highly effective (up to 5 log-fold) against clinically relevant strains of methicillin-resistant S. aureus and E. coli . As a result, the coated surface also significantly reduced biofilm formation. The coatings show good biocompatibility with numerous cell lines as well as low levels of cytotoxicity (ISO 10993–5) and pyrogenicity (ISO 10993–11). The coatings also exhibited strong antioxidant properties toward formed hydroxyl radicals in an in-vitro Fenton reaction. Overall, substitution of chitosan with benzophenone residues is an interesting and important approach to the functionalization of materials used for medical implants that are prone to microbial contamination and mechanical failure. Biocompatible antimicrobial coatings might also be employed in photopatterning methods used in the design of medical devices. Graphical abstract: Image 1 Highlights: Five different chitosan-benzophenone derivatives were synthesized and characterized. Functionalization occurs chemoselective at the chitosan free NH2 group. Coatings show up to log-5-fold reduction in MRSA and E. Coli contamination. Excellent biofilm reduction on the coating of MRSA and E. coli . Low cytotoxicity and low pyrogenicity according to ISO 10993 testing.